Tyrosine Kinase Inhibitors as Antiangiogenic Drugs in Multiple Myeloma - Domenico Ribatti (MDPI AG, 2010)
Tyrosine kinase inhibitors are a new class of anticancer drugs, that are capable of directly interacting with the catalytic site of the target enzyme and thereby inhibiting catalysis. Therapeutically useful tyrosine kinase inhibitors are not specific for a single tyrosine kinase, but rather they are selective against a limited number of tyrosine kinases. The success of imatinib-mesylate (Gleevec®) for the treatment of patients with chronic myeloid leukemia has opened a intensive search for new small molecular compounds able to target other protein tyrosine kinases involved in the malignant transformation. This review article is focused on the use of tyrosine kinase inhibitors as antiangiogenic molecules in the treatment of multiple myeloma.